Zika Virus Neuropathogenesis: The Different Brain Cells, Host Factors and Mechanisms Involved - Komarasamy, Thamil Vaani; Adnan, Nur Amelia Azreen; James, William; Balasubramaniam, Vinod R. M. T. (Frontiers in Immunology, 2022)
Zika virus (ZIKV), despite being discovered six decades earlier, became a major health concern only after an epidemic in French Polynesia and an increase in the number of microcephaly cases in Brazil. Substantial evidence has been found to support the link between ZIKV and neurological complications in infants. The virus targets various cells in the brain, including radial glial cells, neural progenitor cells (NPCs), astrocytes, and microglial and glioblastoma stem cells. It affects the brain cells by exploiting different mechanisms, mainly through apoptosis and cell cycle dysregulation. The modulation of host immune response and the inflammatory process has also been demonstrated to play a critical role in ZIKV induced neurological complications. In addition to that, different ZIKV virus strains have exhibited specific neurotropism and unique molecular mechanisms. This review provides a comprehensive and up-to-date overview of ZIKV-induced neuroimmunopathogenesis by dissecting its main target cells in the brain, and the underlying cellular and molecular mechanisms. We highlighted the roles of the different ZIKV host factors and how they exploit specific host factors through various mechanisms. Overall, it covers key components for understanding the crosstalk between ZIKV and the brain.